2019
DOI: 10.1093/ije/dyz114
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 air pollution and cause-specific cardiovascular disease mortality

Abstract: Background Ambient air pollution is a modifiable risk factor for cardiovascular disease, yet uncertainty remains about the size of risks at lower levels of fine particulate matter (PM2.5) exposure which now occur in the USA and elsewhere. Methods We investigated the relationship of ambient PM2.5 exposure with cause-specific cardiovascular disease mortality in 565 477 men and women, aged 50 to 71 years, from the National Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
153
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(165 citation statements)
references
References 42 publications
5
153
3
4
Order By: Relevance
“…It's well known that PM2.5 affect the airways and the cardiovascular system, it can penetrate deep into lung tissue, causing immune and in ammation response [23][24][25]. Long-time exposure has been correlated with increased risks of chronic diseases, including chronic obstructive pulmonary disease (COPD) that can develop into lung cancer [26,27]. In addition, short-term exposure to PM2.5 is robust associate with increased mortality from various cardiopulmonary diseases, from a nationwide analysis in 272 chinese cities [28].…”
Section: Discussionmentioning
confidence: 99%
“…It's well known that PM2.5 affect the airways and the cardiovascular system, it can penetrate deep into lung tissue, causing immune and in ammation response [23][24][25]. Long-time exposure has been correlated with increased risks of chronic diseases, including chronic obstructive pulmonary disease (COPD) that can develop into lung cancer [26,27]. In addition, short-term exposure to PM2.5 is robust associate with increased mortality from various cardiopulmonary diseases, from a nationwide analysis in 272 chinese cities [28].…”
Section: Discussionmentioning
confidence: 99%
“…Severe air pollution is a major health risk and can lead to large premature mortality (Schraufnagel et al, 2019). Previous studies have shown that PM 2.5 has an adverse impact on human health and long-term exposure to high PM 2.5 concentration environment will lead to various respiratory diseases because -PM 2.5 carries lots of harmful matters and viruses and can go directly into our lungs (Hayes et al, 2019;McGuinn et al, 2019). As reported in the 6 th Edition of COVID-19 Treatment Regimen (Trial Implementation) published by the National Health Commission of the People's Republic of China, COVID-19 is mainly transmitted by direct contact and droplet transmission, and aerosol transmission is also a potential way (Wang and Du, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The risks that entail PM 2.5 or fine particulate have threatened the mortality of human lives and the adverse health effects associated with PM 2.5 made it as a major indicator of air particle pollution by the World Health Organization (WHO, 2005). Reports have shown that worldwide exposure to outdoor PM 2.5 contributed to 4.1 million deaths connected with heart disease and stroke, lung cancer, chronic lung disease, and respiratory infections (Orru et al, 2011;HEI, 2018;Li et al, 2018;Hayes et al, 2019). The increasing epidemiological studies indicate that cardiopulmonary morbidity due to PM 2.5 exposure play a part in the development of diabetes mellitus and adverse birth outcomes (Hu, 2009;Crouse et al, 2012;Kloog et al, 2012;Chen et al, 2013;Burnett et al, 2014;Zanobetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%